Manganese Recovery from Hydrocracking Spent Catalyst Using Citric Acid and Its Kinetics - Petrus, Himawan Tri Bayu Murti; Sari, Dewi Purnama; Yuliansyah, Ahmad Tawfiequrrahman; Mufakhir, Fika Rofieq; Astuti, Widi; Iskandar, Yusuf; Bratakusuma, Danu; Virdhian, Shinta (Universitas Lampung, 2019)
Aiming for recovery and kinetics of manganese from hydrocracking spent catalyst using citric acid, this study has been conducted. In order to justify the performance of citric acid, a comparative study has been conducted using both inorganic and organic acids in the same pH condition of about 1,5 - 2. pH was used as the controlled variable due to the different dissociation degree of the acids. In comparison to that of inorganic acid, the manganese recovery is four times higher when citric acid was applied. Acetic acid performed 33% lower in manganese recovery compared to the citric acid. Moreover, kinetics study was conducted with three varying temperature of 30C, 60C, and 90C. From the resulted data, it can be concluded that the kinetics of mengan leaching from spent catalyst using citric acid is in accordance to the shrinking core model. The controlling step is product diffusion with activation energy (Ea) of about 23.27 kJ/mol calculated using Arrhenius expression. With higher selectivity and leaching reagent which is harmless to the environment, the application of citric acid in manganese leaching from spent catalyst will indeed support the enactment of sustainable development aspect in recycle processing